The Aesthetic Use of the Logical Functions in Kant's Third Critique - Adair, Stephanie (Kantstudien. Ergänzungshefte ;, 2018)
In the third Critique Kant details an aesthetic operation of judgment that is surprising considering how judgment functioned in the first Critique. In this book, I defend an understanding of Kant's theory of Geschmacksurteil as detailing an operation of the faculties that does not violate the cognitive structure laid out in the first Critique. My orientation is primarily epistemological, elaborating the determinations that govern the activity of pure aesthetic judging that specify it as a "bestimmte" type of judgment without transforming it into "ein bestimmendes Urteil". I focus on identifying how the logical functions from the table of judgments operate in the pure aesthetic judgment of taste to reveal "the moments to which this power of judgment attends in its reflection" (CPJ, 5:203). In the course of doing so, a picture emerges of how the world is not just cognizable in a Kantian framework but also charged with human feeling, acquiring the inexhaustible, inchoate meaningfulness that incites "much thinking" (CPJ, 5:315). The universal communicability of aesthetic pleasure serves as the foundation that grounds robust intersubjective relations, enabling genuine connection to others through a shared a priori feeling.